Research priorities and future of alfalfa in Latin America - Vivela, Duarte; Basigalup, Daniel Horacio; Juntolli, Fabrício V.; Ferreira de Paula, Reinaldo (INTA, 2018)
Future actions aimed at the technological development of Latin American’s agrifood and agroindustrial systems should seek to anticipate trends and ensure the permanent adjustment of research and development priorities, viewing innovations inspired by the logic of productive chains, which are increasingly dependent upon knowledge and technology. To ensure quantity and quality for the growing demand of food while preserving natural resources and adding value to the product, it is necessary to invest in research with a transdisciplinary approach in order to manage systems which are increasingly complex and strikingly bound to convergent technologies. The migration of production systems with few activities for those more complex stands out as a strong trend for the next decades. This will certainly require to handle increasingly dynamic processes that will be part of the agribusiness that opens up for the near future.